Artificial Somatosensors: Feedback Receptors for Electronic Skins. (23rd November 2020) - Rahman, Md. Ataur; Walia, Sumeet; Naznee, Sumaiya; Taha, Mohammad; Nirantar, Shruti; Rahman, Fahmida; Bhaskaran, Madhu; Sriram, Sharath
Abstract : Electronic Skins In article number 2000094, Md. Ataur Rahman, Madhu Bhaskaran, Sharath Sriram, and co‐workers demonstrate artificial skin receptors capable of sensing and mimicking the feedback response of somatosensors in skin. The most prevalent skin receptors which relate to pressure, temperature, and pain are presented using a combination of stretchable pressure sensors, phase change oxide thin films, and threshold based resistive switching (memristor) memory elements.